ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA PADA TOPIK SISITEM PERSAMAAN LINIER DUA VARIABEL BERDASARKAN PROSEDUR NEWMAN - delvita rahma sari; Mulia Suryani; Hafizah Delyana (Department of Mathematics Education, Universitas Kuningan, 2022)
The error analysis in this study is the error made by students in solving stories problems on the topic of a two-variable linear equation system based on the Newman procedure. This study uses a descriptive method with a quantitative approach. The subjects of this study were students of class VIII B MTsN 13 Pesisir Selatan. The sampling technique used was purposive sampling. The instruments used to collect data are tests and documentation. The results showed that the errors that were mostly made by students were encoding error of 34.64%, including the high enough category. Furthermore, the process skill error and are 30.46%, including the fairly high category. Meanwhile, the transformation error is 15.23%, including the small category. For the comprehension error of 15.23%, including the small category, and the reading error of 4.64% including the very small category. So, it can be concluded that the mistakes that many students make in story problems are two-variable linear equation system problems, encoding errors of 34.44% and the smallest errors made by students, reading errors of 4.64%.